Growth and Growth hormone – Insulin Like Growth Factor –I (GH-IGF-I) Axis in Chronic Anemias - Soliman, Ashraf T; De Sanctis, Vincenzo; Yassin, Mohamed; Adel, Ashraf (Acta Biomedica Atenei Parmensis, 2017)
Anaemia is a global public health problem affecting both developing and developed countries with major consequences for human health as well as social and economic development. It occurs at all stages of the life cycle, but is more prevalent in pregnant women and young children. Iron deficiency anaemia (IDA) was considered to be among the most important contributing factors to the global burden of disease. Prolonged and/or chronic anemia has a negative effect on linear growth especially during the rapid phases (infancy and puberty). Additionally infants with chronic IDA have delayed cognitive, motor, and affective development that may be long-lasting. In view of the significant impact of chronic anemias on growth, pediatricians endocrinologists and hematologists should advocate primary prevention and screening for growth disturbance in these forms of anemias. The extent of the negative effect of different forms of chronic anemias on linear growth and its possible reversibilty is addressed in this review. The possible mechanisms that may impair growth in the different forms of anemias are addressed with special attention to their effect on the growth hormone (GH) – insulin like growth factor –I (IGF-I).